2020
DOI: 10.21930/rcta.vol21_num3_art:1402
|View full text |Cite
|
Sign up to set email alerts
|

Frecuencia y altura de corte sobre la calidad del Megathyrsus maximus (cv. Gatton panic)

Abstract: El estudio que se presenta a continuación tuvo como objetivo evaluar la frecuencia e intensidad de la calidad nutricional en la materia seca (MS) del pasto Megathyrsus maximus (cv. Gatton panic), y fue desarrollado en la Cabaña Doña Anita, provincia del Chaco, Argentina. Se empleó un diseño completamente al azar con un arreglo factorial de 2 alturas de corte (A = 0,15 y 0,30 m), 3 frecuencias (F = 30, 45 y 90 días) y 2 tiempos (T = 90 y 180 días) con cinco repeticiones para cada uno (60 unidades experimentales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
1
3
1
Order By: Relevance
“…In the present study, an increase in LW and LL of M. maximus with the advance of the phenological stage was NDF content in blades increased from the first to the third cut, while ADF increased from first to second cut and then remained constant at the late stage except for the Vencedor genotype. These findings differ from those of Schnellmann et al 35 who reported significant increases in these parameters between different cutting intervals (30, 45, and 90 days). They mention that NDF is a fraction whose increase is associated with the advance of the phenological stage of the plant.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the present study, an increase in LW and LL of M. maximus with the advance of the phenological stage was NDF content in blades increased from the first to the third cut, while ADF increased from first to second cut and then remained constant at the late stage except for the Vencedor genotype. These findings differ from those of Schnellmann et al 35 who reported significant increases in these parameters between different cutting intervals (30, 45, and 90 days). They mention that NDF is a fraction whose increase is associated with the advance of the phenological stage of the plant.…”
Section: Discussioncontrasting
confidence: 99%
“…NDF and ADF content in stems increased from the first to the second cut and then remained constant at the late stage except for Vencedor and Mutale genotypes. Our results differ from those of Méndez-Martínez et al 34 and of Schnellmann et al 35 who found that these nutritional parameters increased as regrowth age advanced. In agreement with Stabile et al, 36 we observed genotypic variations for these nutritional parameters.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Análisis de Van Soest de cuatro gramíneas del estado de Jalisco, g (100 g) -1 en base seca. Para FDN en Megathyrsus maximus cv Guinea se han reportado valores de 68.36 g (100 g) -1 (Ardila y Laredo, 1984), 72.7 g (100 g) -1 (Reyes et al, 2009), 62.3 g (100 g) -1 (Schnellmann et al, 2020) y 80.2 g (100 g) -1 (Bautista-Tolentino et al, 2011). En el presente estudio se obtuvo un valor de 74.79 g (100 g) -1 , similar al obtenido por Reyes et al (2009).…”
Section: Fibra Detergente Neutro (Fdn)unclassified